Greenland Shark (Somniosus microcephalus) Stomach Contents and Stable Isotope Values Reveal an Ontogenetic Dietary Shift - Nielsen, Julius; Christiansen, Jørgen Schou; Grønkjær, Peter; Bushnell, Peter; Steffensen, John Fleng; Kiilerich, Helene Overgaard; Præbel, Kim; Hedeholm, Rasmus (Frontiers in Marine Science, 2019)
Current knowledge on the feeding ecology of the Greenland shark (Somniosus microcephalus), a potential top predator in arctic marine ecosystems, is based on small sample sizes as well as narrow size ranges of sharks. Therefore, potential size-related feeding patterns remain poorly documented. Using stomach content data (N=88) and stable isotope values of white muscle tissue (N=40), this study evaluates the diet in sharks ranging in size from 81 cm to 474 cm (total length). The importance of prey categories (‘Fish’, ‘Mammal’, ‘Squid’, ‘Crustacean’ and ‘Other’) was evaluated based on the reconstructed prey biomass of the stomach contents. Stable isotopes values of δ13C and δ15N ranged between -14.4‰ to -19.9‰ and 11.8‰ to 17.2‰, respectively. The importance of each prey category was estimated by the Index of Relative Importance (IRI). Our findings suggest that the smallest Greenland sharks (<200 cm) feed on lower trophic level prey, predominantly squids. Larger sharks (>200 cm) mainly feed on higher trophic level prey such as seals, epibenthic and benthic fishes including gadoids (Gadidae), skates (Rajidae), righteye flounders (Pleuronectidae), lumpfish (Cyclopteridae), wolffish (Anarhichadidae), and redfish (Sebastidae). Redfish were, however, only found to be important in the largest sharks sampled (>400 cm). In addition to demonstrating ontogenetic shits in their feeding preferences, this study supports that Greenland sharks are capable of active predation on fast swimming seals and large fishes.